Epithelial Sodium Channel-α Mediates the Protective Effect of the TNF-Derived TIP Peptide in Pneumolysin-Induced Endothelial Barrier Dysfunction - Czikora, Istvan; Alli, Abdel A.; Sridhar, Supriya; Matthay, Michael A.; Pillich, Helena; Hudel, Martina; Berisha, Besim; Gorshkov, Boris; Romero, Maritza J.; Gonzales, Joyce; Wu, Guangyu; Huo, Yuqing; et al. (Frontiers in Immunology, 2017)
Background: Autolysis and antibiotic-mediated lysis of S. pneumoniae induces release of the pore-forming toxin, pneumolysin (PLY), which is a prominent cause of acute lung injury in pneumonia. PLY inhibits alveolar liquid clearance (ALC) and severely compromises alveolar-capillary barrier function, leading to permeability edema. As a consequence, alveolar flooding occurs, which can precipitate lethal hypoxemia by impairing gas exchange. The alpha  subunit of the epithelial sodium channel (ENaC) is crucial for promoting Na+ reabsorption across Na+-transporting epithelia. However, it is not known if human lung microvascular endothelial cells (HL-MVEC) also express ENaC-alpha and whether this subunit is involved in the regulation of capillary barrier function. Methods: The presence of alpha, beta and gamma subunits of ENaC and protein phosphorylation status in HL-MVEC were assessed in Western blotting. The role of ENaC-alpha in endothelial monolayer resistance was examined by depletion of the subunit using specific siRNA and by employing the TNF-derived TIP peptide, a specific activator, which directly binds to ENaC-alpha. Results: HL-MVEC express all three subunits of ENaC, as well as ASIC1a, which has the capacity to form hybrid non-selective cation channels with ENaC-alpha. Both TIP peptide, which specifically binds to ENaC-alpha and the specific ASIC1a activator MitTx significantly strengthened barrier function in PLY-treated HL-MVEC. ENaC-alpha depletion significantly increased sensitivity to PLY-induced hyperpermeability and in addition, blunted the protective effect of both the TIP peptide and MitTx, indicating an important role for ENaC-alpha and for hybrid NSC channels in barrier function of HL-MVEC. TIP peptide blunted PLY-induced phosphorylation of both calmodulin dependent Kinase II (CaMKII) and of its substrate, the actin-binding protein filamin A (FLN-A), requiring the expression of both ENaC-alpha and ASIC1a. Since non-phosphorylated FLN-A promotes ENaC channel open probability and blunts stress fiber formation, modulation of this activity represents an attractive target for the protective actions of ENaC-alpha in both barrier function and liquid clearance. Conclusions: Strategies aiming to activate endothelial NSC channels that contain ENaC-alpha should be further investigated as a novel approach to improve barrier function in the capillary endothelium during pneumonia.